THE BRAIN AS A MULTI-LAYERED MAP. SCALES AND REFERENCE POINTS FOR PATTERN RECOGNITION IN NEUROIMAGING - Zaleshina, Margarita; Zaleshin, Alexander (European Journal of Geography, 2017)
In this paper, we provide an overview of brain mapping in neuroscience and describe the application of spatial data processing techniques to represent the brain as a multi-layered map.Anatomical reference points (landmarks) are determined from the topological properties of the brain, including the shapes of sulci, gyri, and fissures. Functional reference points are calculated by measured parameters of brain activity. Linking experimental results with spatial and temporal reference points is a necessary step for performing a comparative analysis of heterogeneous data regarding brain structures and activity. Using reference points helps define coordinate systems and scales, highlight points of interest and regions of interest, create templates, and classify data. The paper shows that spatial analysis is a convenient approach to pattern recognition in neuroimaging. We also discuss the role of extrinsic behavior landmark stimuli and intrinsic brain structural elements such as place cells and grid cells in navigation tasks.